Effects of different addition levels of CHM-JM113 on growth performance, antioxidant capacity, organ index, and intestinal health of AA broilers - Fu, Guanhua; Zhang, Mengyu; Huang, Yuanyuan; Han, Runyu; Qi, Kaixuan; Yin, Lidong; Zhao, Dongchen; Huang, Yueyan; Ma, Tenghe; Wang, Lihong (Frontiers in Veterinary Science, 2024)
The purpose of the present study was to investigate the effects of different levels of a Chinese herbal medicine formulation combined with JM113 (CHM-JM113) on growth performance, antioxidant capacity, organ index, and intestinal health of AA broilers. The AA broiler chicks were randomly allocated to 5 treatments as follows: a basic diet for the control group, the basic diet supplemented with 0.25% CHM-JM113, 0.5% CHM-JM113, 1% CHM-JM113 and 2% CHM-JM113 for the treatment group, respectively. The results showed that the addition of CHM-JM113 to the diet significantly reduced the mortality (P < 0.01) and improved the European Broiler Index (EBI) (P < 0.05), whereas it had no significance on growth performance of AA broilers (P ＞ 0.05 ). Comparing the control group, 0.5 % and 1 % CHM-JM113 group significantly improved the organ index of liver, spleen and bursa (P < 0.05). In terms of intestinal morphology and structure, the addition of different levels of CHM-JM113 increased VH and VH/CD ratio, decreased CD in the small intestine compared to the control group, with 1% and 2% of the additive dose being more effective (P < 0.05).Chinese herbal medicine and probiotics as natural antioxidants also significantly increased the content of SOD in serum of 21-day-old broilers (P < 0.01), and significantly decreased the content of MDA in serum (P < 0.01). At 42 days of age, the addition of 1 % and 2 % CHM-JM113 significantly increased the content of SOD (P < 0.01) and significantly decreased the content of MDA in the organism (P < 0.01), accompanied by a significant increase in T-AOC and CAT content. In the study of the effect of CHM-JM113 on intestinal immunity, compared with the control group, we found that 1% or 2% CHM-JM113 had a better effect on the expression of occludin and claudin-1 in the intestinal segments of broilers (P < 0.05). For the expression of GATA-3, 0.5% CHM-JM113 may have a better effect (P < 0.05). CHM-JM113 may be used as an antibiotic alternative in broiler production.